(untitled) (Journal of Educational Sciences, 2018)
The content of art and educational activities in the prevention of abnormal domains in society are identified by the authors based on survey results after piloting the art- pedagogical session, conducted with adolescents and young people of 14 – 19 years old. By analyzing the questionnaire data the authors, argue that the establishment of creativity contributes to promotion of individual in society, the development of all the senses, memory, perception, will, imagination, intuition, stress relief, increase of emotional tone, confidence, positive attitude. The statements of the respondents in the open-ended questionnaire with regard to materials of art-pedagogical sessions allow authors to claim that work on the paintings, sculpture and other methods of working in art-pedagogy – a safe way to discharge destructive emotions. They enable to work out the thoughts and emotions that people used to suppress, support a creative self-expression and develop the imagination, intuition, reduce negative emotional state and its expressions. Thus, the authors conclude that the potential of art-pedagogy and art- therapy in the context of the prevention of suicidal behavior and related domains is large enough that the application of appropriate techniques in mass education and upbringing largely predetermines the solution of the problem of early prevention of suicidal tendencies of adolescents and young people in Kazakhstan. This article presents the results of the grant project of the Ministry of Education and Science of the Republic of Kazakhstan “Art – pedagogy and art-therapy for the prevention of suicidal behavior of young people in Kazakhstan: development of scientific bases and practical technology” in the aspect of piloting the art-technologies by the authors. Key words: art therapy, art-pedagogy, art-techniques, art-pedagogical session, art- technology, a positive attitude.